Perancangan Terowongan Angin Rangkaian Terbuka Dengan Sistem Piv (Particle Image Velocimetry) - rendi, rendi; Firman, Muhammad; Hartadi, Budi; Arifin, Jainal; Irfansyah, Muhammad (Proklamasi 45 University, 2024)
This research aims to design an open circuit wind tunnel with a piv (particle image velocimetry) system. This particle image velocimetry system was chosen because this system has the advantage of being easy to make and the equipment used is not too complicated. The method used in this design is a mathematical calculation method with. This tunnel is designed to have dimensions of 8 meters long, 1.75 meters wide and 1.75 meters high. With a maximum planned wind speed of 30 m/s. The design results state that the head loss in the test section is 1.28 m, in the contraction chamber is 0.52 m and the head loss in the diffuser is 0.49 m so the total head is 2.29 m so a pump power of 11.94 hp is needed to be able to simulate a maximum wind flow of 30 m. /s